Is there life after sixth grade? - McGuire, Leslie; Henry, Paul, 1956- (Mahwah, N.J. : Troll Associates, 1990)
When her eccentric dress keeps her out of the class yearbook picture, sixth-grader Amy decides to create, with the help of her best friend Anthony's photographic skills, an alternative yearbook composed of candid shots of her classmates and teachers.
4.7
3-6
3-6
School Library Journal
Keywords: Individuality -- Fiction; Schools -- Fiction; School stories